2019
DOI: 10.1371/journal.pone.0220654
|View full text |Cite
|
Sign up to set email alerts
|

Serum cystatin C levels relate to no-reflow phenomenon in percutaneous coronary interventions in ST-segment elevation myocardial infarction

Abstract: Background/Aim No-reflow is a serious and frequent event during primary percutaneous coronary intervention (PPCI) for acute ST segment elevation myocardial infarction (STEMI). The aim of this study was to identify possible predictors for no-reflow. Patients and methods We investigated 218 patients with acute anterior STEMI who underwent PPCI from December 2016 to December 2018. No-reflow was defined as a coronary TIMI flow grade of � 2. TIMI flow grade 3 was defined as normal reflow. Results In our study, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 37 publications
0
13
0
1
Order By: Relevance
“…35,36 Quisi et al 37 determined a close relationship between baseline serum rheumatoid factor and NR phenomenon in patients with acute STEMI. Cheng et al 16 demonstrated higher levels of d -dimer and cystatin C in patients with NR in their study consisting of 218 patients with acute anterior MI. Among the biomarkers that are shown to be associated with NR and require a special kit are calprotectin and serum soluble suppression of tumorigenicity.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…35,36 Quisi et al 37 determined a close relationship between baseline serum rheumatoid factor and NR phenomenon in patients with acute STEMI. Cheng et al 16 demonstrated higher levels of d -dimer and cystatin C in patients with NR in their study consisting of 218 patients with acute anterior MI. Among the biomarkers that are shown to be associated with NR and require a special kit are calprotectin and serum soluble suppression of tumorigenicity.…”
Section: Discussionmentioning
confidence: 93%
“…4,5 Studies have shown that age, the presence of diabetes and hypertension (HT), target vessel diameter, length of the lesion, thrombus load, and several laboratory parameters may affect the development of NR. 615 Cheng et al 16 demonstrated higher levels of d -dimer and cystatin C in patients with NR in their study consisting of 218 acute anterior myocardial infarction (MI). In another study by Zhang et al, 17 HA 2 DS 2 -VASc-HSF score, defined as the new onset of congestive heart failure, hypertension, age (≥65 = 1 point, ≥75 = 2 points), diabetes, stroke/transient ischemic attack (2 points), and vascular disease (peripheral arterial disease, previous MI, and aortic atheroma), hyperlipidemia (H), smoking (S), and a family history of coronary heart disease (F), which includes hyperlipidemia, smoking, and family history for coronary artery disease in addition to classical score, was found to be an independent predictor of NR in patients with ST-elevation myocardial infarction (STEMI) treated with primary PCI (pPCI).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Sarli et al found that optimal D-dimer cut-off value for predicting NR was 549 µg/l [25]. In 218 STEMI patients, Cheng et al [24] found that NR patients were older, diabetics, with longer pain-to balloon time, lower blood pressure, higher platelet counts and higher levels of D-Dimer and Cystatin C than patients without NR.…”
Section: Discussionmentioning
confidence: 98%
“…The pathogenesis of NR remains unclear, but it is likely to be multifactorial, including endothelial damage platelet and clotting activation leading to thrombus formation at the level of small vessels [20]. Few studies investigated the occurrence of NR in STEMI patients undergoing PCI and its relationship with D-Dimer [15,[21][22][23][24][25]. In 229 consecutive STEMI patients, X. Gong et al [23] found that a D-dimer value of 530 ng/ml was associated with postprocedural NR, with 85.7% of sensitivity and 67.7% of speci city (area under the curve [AUC] = 0.78; p=0.049).…”
Section: Discussionmentioning
confidence: 99%
“…В описанном случае пациент С. после появления болевого синдрома продолжил бежать еще час, и не тотчас же после финиша марафона обратился за медицинской помощью. Во многих работах, в частности, в исследовании C. Cheng и соавт., описана взаимосвязь позднего поступления пациентов с ИМпST в стационар с развитием при ЧКВ феномена no-reflow [10].…”
Section: Discussionunclassified